2023
DOI: 10.3389/fpsyg.2023.1110612
|View full text |Cite
|
Sign up to set email alerts
|

Dinos and GoPros: Children’s exploratory behaviors in a museum and their reflections on their learning

Abstract: Research in both laboratory and museum settings suggests that children’s exploration and caregiver–child interaction relate to children’s learning and engagement. Most of this work, however, takes a third-person perspective on children’s exploration of a single activity or exhibit, and does not consider children’s perspectives on their own exploration. In contrast, the current study recruited 6-to 10-year-olds (N = 52) to wear GoPro cameras, which recorded their first-person perspectives as they explored a din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It is an open question whether the parent-child interactions would reflect our observed patterns in more natural museum contexts where multiple families might engage with an exhibit at once. Additionally, although several studies have documented that the parent-child interaction style coding we used to describe the dyads' goal setting generalizes across contexts other than museum exhibits (e.g., Medina & Sobel, 2020;Sobel & Stricker, 2022;Weisberg et al, 2023), to our knowledge, there have not been investigations considering the observed temporal dynamics between parental explanatory talk and children's exploratory behaviors. We suspect that the observed temporal relations will generalize to parentchild interactions outside of museum contexts; however, future research should directly test how parents and children interact with one another in other informal learning settings.…”
Section: Limitations Of the Present Investigationmentioning
confidence: 99%
“…It is an open question whether the parent-child interactions would reflect our observed patterns in more natural museum contexts where multiple families might engage with an exhibit at once. Additionally, although several studies have documented that the parent-child interaction style coding we used to describe the dyads' goal setting generalizes across contexts other than museum exhibits (e.g., Medina & Sobel, 2020;Sobel & Stricker, 2022;Weisberg et al, 2023), to our knowledge, there have not been investigations considering the observed temporal dynamics between parental explanatory talk and children's exploratory behaviors. We suspect that the observed temporal relations will generalize to parentchild interactions outside of museum contexts; however, future research should directly test how parents and children interact with one another in other informal learning settings.…”
Section: Limitations Of the Present Investigationmentioning
confidence: 99%